ANALISA DAMPAK PENERAPAN MANAJEMEN PROYEK DAN EFEKTIFITAS PEKERJA TERHADAP KEBERHASILAN PENYELESAIAN PROYEK PADA PEMBANGUNAN PERUMAHAN BERSUBSIDI PESONA PRIMA 7 RAJAMANDALA DEVELOPER PT. KREASI PRIMA NUSANTARA - Yusri Yusri; Yudi Wibowo (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the impact of knowing whether project management has been carried out properly and correctly in subsidized housing development projects and to find out whether the company has implemented Employee Performance Effectiveness properly and correctly in implementing the Pesona Prima 7 Rajamandala subsidized housing project. Methods of data collection by observation, surveys, and interviews conducted with 3 (three) informants. The results of the study show that the company has implemented project management well in terms of the use of management tools and techniques, overcoming obstacles in implementing project management and efforts to improve project management that has been implemented. And the effectiveness of workers who have a significant impact on the success of the Pesona Prima 7 Rajamandala subsidized housing development project.